MENINGKATKAN HASIL BELAJAR DENGAN MENERAPKAN MODEL PEMBELAJARAN INKUIRI PADA MATA PELAJARAN PKN SISWA KELAS IV DI SD INPRES SRITABAANG - Kusumayanti, Dian; Anta, I Made Nuhari; Hariani, Ni Made Mega (JATMIKA : Journal Education and Learning of Elementary School, 2024)
This study aims to improve student learning outcomes in civic education subjects using the inquiry model in class IV SD Inpres Sritabaang. The method used in this study is a class action research method (PTK) through two cycles, where each cycle consists of planning, implementation of actions, observation and reflection. The data taken is quantitative and qualitative. Quantitative data that is learning outcomes data obtained from the test results and qualitative data, namely data from observations obtained from observation of learning situations. The results of the first cycle of research were completed by 14 people and not completed by 8 people with a percentage of 71,59 classical absorption and 63,63% percentage classical completeness. learning outcomes in the second cycle obtained 20 people completed individually and not completed by 2 people with a percentage of 79,31% classical absorption and 90,91% percentage classical completeness. Thus it can be concluded that the use of inquiry learning model can improve student learning outcomes in class IV SD Inpres Sritabaang on subjects education civic.